Hard X-Ray, Gamma-Ray, and Neutron Detector Physics XX 2018
DOI: 10.1117/12.2320676
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Cd0.90-xMnxZn0.10Te (x = 0.10, 0.20) crystals grown by Vertical Bridgman method

Abstract: The correlation between Cd0.90-xMnxZn0.10Te (CMZT) melt state and structural properties of the crystals, grown by vertical Bridgman method, was investigated. The Cd0.9-xMnxZn0.1Te crystals with various Mn compositions (x = 0.1 and 0.2) were grown by a two-step method from high-purity elemental components. We have conducted a series of crystal growth runs with different degrees of melt superheating over the alloy's melting temperature. We obtained ingots with various crystalline structures and properties. It wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…These values indicated that with MnTe concentration increasing from 10% to 20 % increased the band-gap value by 0.011 eV per 1% of MnTe. The increase of ZnTe concentration from 10% to 15 % changed the band-gap value of CMZT crystals from 1.67 eV [15] to 1.73 eV for Cd0.90-yMn0.10ZnyTe and from 1.78 eV [15] to 1.84 eV for Cd0.80-yMn0.20ZnyTe (0.012 eV per 1% ZnTe). Thus, even a slight increasing of MnTe and ZnTe concentration led to increasing of the band-gap value.…”
Section: Srnl-sti-2021-00357mentioning
confidence: 97%
“…These values indicated that with MnTe concentration increasing from 10% to 20 % increased the band-gap value by 0.011 eV per 1% of MnTe. The increase of ZnTe concentration from 10% to 15 % changed the band-gap value of CMZT crystals from 1.67 eV [15] to 1.73 eV for Cd0.90-yMn0.10ZnyTe and from 1.78 eV [15] to 1.84 eV for Cd0.80-yMn0.20ZnyTe (0.012 eV per 1% ZnTe). Thus, even a slight increasing of MnTe and ZnTe concentration led to increasing of the band-gap value.…”
Section: Srnl-sti-2021-00357mentioning
confidence: 97%
“…Before use, the CdTe single crystals were prepared with different crystal orientations following the ''Bridgman'' synthesis method, described elsewhere. [55][56][57][58][59] The measured crystals have no ligands on top, and no treatment has been done except removing these oxide layers by cutting the crystals or using the Ar ion sputtering process.…”
Section: Experimental Procedures Materialsmentioning
confidence: 99%